Petrochemical Industries - A.S Nasution; Abdul Haris; Morina Morina; Leni Herlina (Testing Center for Oil and Gas LEMIGAS, 2010)
Petrochemical processes begin with relatively few basic raw materials, expand into a complex network of chemicals and converge into materials that serve specific functions as consumer products. Then raw material base for the petrochemical industry primarily depends upon the type of intermediates and final products required by industry and consumer. Almost all petrochemicals are derived from three sources: synthesis gas, olefin and aromatic. Production of those three petrochemical sources and the derivative chemicals are described briefly